Bioactivity and action mechanism of green propolis against Pythium aphanidermatum - Moreira Pazin, Wallance (2019)
We have established how natural compounds from green propolis collected by the species Apis mellifera act against the growth of Pythium aphanidermatum. On the basis of mass spectrometry (Q-ToF MS), we determined that Artepillin C, the major constituent of green propolis, underlies the effect and displays activity against P. aphanidermatum at a minimal inhibitory concentration of 750 µg.mL-1. Biophysical studies based on model membranes showed that this inhibitory effect may be linked with a membrane-related phenomenon: Artepillin C increases the permeability of membranes with relatively high fluidity in their lateral structure, a feature that is in line with the lipid composition reported for the cytoplasmic membrane of P. aphanidermatum. Therefore, the present study supports the use of the effective and inexpensive green propolis to control the impact of the dangerous phytopathogen P. aphanidermatum on agriculture.